Visual uncertainty models through the political lens of the visual arts in the eras of Bush and Trump. Issue 4 (2nd October 2019) - Friedman, Alon
Abstract: In today's political and rhetorical landscape, many politicians use Twitter as their communication platform of choice. President Donald Trump is one of the best-known Twitter users. The media often analyze Trump's tweets, and several artists have attempted to interpret them through visualizations. One of the leading visual artists to do so is Erin Gallagher. During the presidency of George W. Bush, visualization was also used to interpret political messages, specifically in work by Mark Lombardi. As controversy surrounding social media's truthfulness has escalated, it seems useful to consider how visual uncertainty has been treated in work by Lombardi and Gallagher. This study asks the following questions: What do these the two leading approaches to visual uncertainty contribute to an examination of works by Erin Gallagher and Mark Lombardi? What does a theoretical analysis reveal about common design features in the work of these artists? The comparison undertaken here shows that, regarding visual precision and credibility, it is difficult to evaluate Gallagher's work. Future studies should examine whether visual grammar theory can add more insight into these artists' visual arguments.